SIRT1 exhibits antioxidative effects in HT22 cells induced by tert‐butyl alcohol. Issue 2 (14th November 2017) - Ma, Junxiang; Song, Dongmei; Zhang, Yuanyuan; Chen, Li; Zhang, Shixuan; Jia, Jiaxin; Chen, Tian; Guo, Caixia; Tian, Lin; Gao, Ai; Niu, Piye
Abstract: Tertiary butyl alcohol (TBA) is a principal metabolite of methyl tertiary‐butyl ether (MTBE), a common pollutant worldwide in the ground or underground water, which is found to produce nervous system damage. Nevertheless, few data regarding the effects of TBA has been reported. Studies indicated that oxidative stress plays a pivotal role in MTBE neurotoxic mechanism. Sirtuin 1 (SIRT1) has been reported to exert a neuroprotective effect on various neurologic diseases via resistance to oxidative stress by deacetylating its substrates. In this study, we examined levels of oxidative stress after exposure to TBA for 6 h in HT22 cells and HT22 cells with SIRT1 silencing (transfected with SIRT1 siRNA) or high expression (preconditioned with agonists SRT1720). We found that TBA activated oxidative stress by increasing generation of intracellular reactive oxygen species (ROS), malondialdehyde (MDA) and Oxidized glutathione (GSSG), and decreasing contents of superoxide dismutase (SOD) and glutathione reductase (GSH). In additional, levels of TBA‐induced oxidative stress were aggravated when SIRT1 silenced but alleviated when SIRT1 enhanced. Our study indicated that SIRT1 mitigated oxidative stress induced by TBA.